Minat Masyarakat Palembang Terhadap Pemilihan Tata Rias Pengantin Pada Pelaksanaan Pernikahan: . - Kusnaedi, Sabrina Nurhaliza; Usodoningtyas, Sri; Megasari, Dindy Sinta; Faidah, Mutimmatul (Program Studi Pendidikan Tata Rias, 2025)
Palembang people's interest in the selection of bridal makeup in the implementation of marriage. The purpose of this study was to determine the public interest in Siger Sunda bridal makeup in Palembang and the factors that influence the interest of Palembang people related to the cultural customs of Palembang society. This research method is observation, interview and questionnaire method conducted in Palembang city, Seberang Ulu I and II sub-districts. Data analysis techniques using descriptive with quantitative methods, which are intended to describe the accurate state or facts of the observed object as many as 50 brides-to-be with Total Sampling technique. The results of this study indicate that the interest of prospective brides in the selection of Sundanese Siger makeup in Seberang Ulu I and II Districts is the most dominant indicator of internal factors with high criteria as much as 0.2%. Based on these results, the average interest in internal factors of prospective brides in choosing Sundanese Siger makeup is 79% with high criteria. Prospective brides choose makeup that is attractive and suits their personality such as Sundanese Siger, which reflects beauty. However, cost is also an important consideration for choosing Siger Sunda makeup because it is simpler and more economical. Keywords: Palembang Community Interest, Culture, Aesan Gede Bridal Makeup.